Pengaruh Kualitas Produk, Kualitas Pelayanan Dan E-Wom Terhadap Keputusan Menginap Di Whiz Prime Hotel Kelapa Gading Jakarta - Shifa Hayati; Parlagutan Silitonga (Human Capital Development, 2023)
This study aims to examine the effect of Product Quality, Service Quality, and Electronic Word Of Mouth (E-WOM) on the decision to stay at Whiz Prime Hotel, type m = quantitative research by distributing questionnaires to Whiz Prime Hotel customers which are then processed using the PLAS-SEM method with the help of PLS Software. The results obtained in this study are Product Quality, Service Quality, and Electronic Word Of Mouth (E-WOM) have a p-value smaller than 0.05. This means that of the three variables tested, all three have a positive and significant influence on the Decision to Stay at Whiz Prime Hotel Kelapa Gading Jakarta.